ETHNOMATHEMATICS IDENTIFICATION IN BATU URIP COMMUNITY ACTIVITIES TO IMPLEMENT MATHEMATICAL CONCEPTS - Dwi Yanti; Drajat Friansyah; Sarkowi (Universitas Muhammadiyah Bengkulu, 2025)
Culture is something that has been inherent in everyday life for generations, because culture is a complete and comprehensive unity that applies in a community, so that it allows for mathematical concepts embedded in mathematical practices or activities. As we know that mathematics is a frightening learning for students, besides being frightening, there are still many students who feel anxious when learning mathematics, this shows that students' mathematics learning is not meaningful, so that students' understanding of the concept is still very weak. The purpose of this study was to identify ethnomathematics contained in the activities of the Batu Urip community. This research is a qualitative descriptive study using ethnographic methods. This research was conducted in the Batu Urip sub-district, Lubuklinggau Timur I district, Lubuklinggau city. The object of this study is the daily activities carried out by the Batu Urip community in buying and selling activities such as weight measurements and grouping of goods. The results of the study indicate that in the activities of the community in selling and measuring the weight of vegetables, fruits, and rice, there are ethnomathematics elements that can be used in learning mathematics related to culture in everyday life. The concepts found are the concept of a linear equation system and its mathematization process, and the concept of function limits such as 1 rice canting, 1 banana comb, 1 kebat and 1 vegetable cup.. Keywords: Ethnomathematics, mathematical concepts, Batu urip